Polycyclic aromatic hydrocarbon removal from petroleum sludge cake using thermal treatment with additives - Edward Nixon Pakpahan (2018)
Petroleum sludge is a hazardous waste that contains various organic compounds including polycyclic aromatic hydrocarbons (PAHs) which have carcinogenic-mutagenic and toxic characteristics. This study focuses on the thermal treatment (indirect heating) of petroleum sludge cake for PAH degradation at 250, 450, and 650 °C using Ca(OH)2+NaHCO3as an additive. The treatment was conducted in a rotary drum electric heater. All experiments were carried out in triplicate. Concentrations of the 16 priority PAHs in gas (absorbed on Amberlite XAD-4 adsorbent), particulate (on quartz filter) and residue phases were determined using gas chromatography-mass spectrometry (GC-MS). The samples were extracted with acetonitrile by ultra-sonication prior to GC-MS analysis. The use of additive was beneficial and a temperature of 450 °C was suitable for PAH degradation. Low levels of PAH emissions, particularly carcinogenic PAH and toxic equivalent concentration (ΣTEC), were observed in gas, particulate and residue phases after treatment. © 2013 Copyright Taylor and Francis GRouép, LLC.